Вы находитесь на странице: 1из 22

2.

2.1.
n
n
dx k
=
a kj x j , k = 1, n ,
(2.1)
dt
j =1

a kj = const .

x1 (t )

x 2 (t )
- x =
...

x (t )
n

( )

A = a kj , (2.1)

dx
= Ax.
dt

(2.2)

2.2.
(2.1) n
x11 (t )
x12 (t )
x1n (t )

x 21 (t ) x 22 (t )
x 2 n (t )
x1 =
, x2 =
, ... , x n =
(2.3)
...
...
...

x (t )
x (t )
x (t )
n1
n2
nn
.
(2.2)
18

x (t ) = C1 x1 (t ) + C 2 x 2 (t ) + K + C n x n (t ) ,
(2.4)
C1 , C 2 , K , C n - .
2.3.
(
).
(2.2):
1) A ,

(2.5)
det ( A E ) = 0 .
1 , 2 ,..., n (2.5), , .
, r
h
r
r r
(2.6)
Ah = h , h 0 .
2.1) (2.5) , .
r
r r
A : Ahm = m hm , hm 0 , m = 1, n .

- x m = hm e mt , m = 1, n (2.2).
(2.2) ( C m )
n

r
(2.8)
x=
C m hm e m t .

m =1

2.2) (2.5) , .
, z = x + iy ,
x, y R , -

19

Re z = x , Im z = y . , e ( + i )t = e t (cos t + i sin t ) .
(2.5)
= + i , = i
( ).

(2.2) x (t ) = h e t x (t ) = h e t .
, , A ,

x (t ) + x (t )
x x , , x1 (t ) =

x (t ) x (t )
, x1 (t ) = Re x (t ) x 2 (t ) = Im x (t ) .
x 2 (t ) =
2i
. ,

h ,


x1 (t ) = Re h e t

x 2 (t ) = Im h e t , .

.., i -
(2.5), ,
,
20



x = C1 x1 (t ) + C 2 x1 (t ) = C1 Re h e t + C 2 Im h e t ,

(2.9)

C1 , C 2 - , h - , = + i .
2.3) . A n . (2.2) .
A , ,
r r
r
h1 , h2 ,..., h p ,
r
r
r r
Ah1 = h1 ,
h1 0,
r
r
r
Ah2 = h2 + h1 ,
r
r
r
(2.10)
Ah3 = h3 + h2 ,
.......................
r
r
r
Ah p = h p + h p 1 .
r r
r
r
h1 - , h2 , h3 ,..., h p -
.
(2.10)
r r
r r
( A E )h1 = 0, h1 0,
(2.11)
r
r
( A E )hk = hk 1 , k = 2, p.
r r
r
h1 , h2 ,..., h p p r r
r
x1 , x 2 ,..., x p (2.2):

21

r
r
x1 = e t h1 ,
r
t r r
x 2 = e t h1 + h2 ,
1!

r
t2 r t r
r
x 3 = e t h1 + h2 + h3 ,
(2.12)
1!

2!
.................................
r
t p 1 r
r
t p2 r
t r
x p = e t
h1 +
h2 +...+ h p 1 + h p .
( p 2)!
1!

( p 1)!
.
r
(2.12). h1 ,
r
r
x1 = e t h1 . e t ,
(2.12) t
, .
,
A .
,
p,

kr
r
r
x (t ) =
e t C l(r ) xl(r ) (t ) ,

(r )

(r )

l =1

C1 , C 2 , K , C k(rr ) - ,

= p.

, A , ,
(2.12)
(2.2).

22

2.4.


r
r r
dx
= Ax + f ,
(2.13)
dt
,
(2.1)
A = a kj . (2.4) -

( )


C m , m = 1, n , C m (t ) :
r
x (t ) =

r
C (t )x (t ) .
m

(2.14)

m =1

r
r
n
n
dx (t )
dC m (t ) r
dx (t )
=
x m (t ) + C m (t ) m
dt
dt
dt
m =1
m =1

(2.13).
..
r
n
dx m (t ) n
r
=
C m (t )Ax m (t ) ,
C m (t )
dt
m =1
m =1

dC m (t )
, m = 1, n :
dt
n
v
dC m (t ) r
x m (t ) = f .
dt
m =1

(2.15)

C m (t ) , m = 1, n , , (2.15)
dC m (t )
, m = 1, n .
dt
, C m (t ) , ..
C m (t ) , (2.14) . 23

(2.13) ,
, , .
2.5. ,
2.1. (2-24) x& = 5 x y 4 z

y& = 12 x + 5 y + 12 z , (1 = 1, 2,3 = 1) .
z& = 10 x 3 y 9 z

5 1 4

c A = 12 5 12 .
10 3 9

1. :
)
A , )
A .
r r
1 = 1 , ( A 1 E )h1 = 0 .
: (n ) + (m ) ,
, n- n- m-
.

24

1
(2 )
6
(3 ) (1)

6 1 4

6 12
A 1 E = 12
10 3 8

6 1 4

1
2
2
4 2 4

2 1 0
2 1

(2 )+ (1)

2 1 2 0 2
0 0 0
0 0

1 0
2 0 1
1
2
(1)

2
0 1
1 ,
0 1 1
0 0 0
0 0
0

1
1
r r t
h1 = 2 x1 = 2 e
2
2


r r
2,3 = 1 , ( A 2 E )h2 = 0 .
(1)+ 2(2 )
(3)+ 2(2 )

A 2 E =
(1)+ (2 )
(3 )+ 3(2 )

4 1 4

4
12
12
10 3 10

1 0 1

3 1 3
1 0 1

1
(2 )
4

(2 )+ 3(1)
(3 ) (1)

(1) 1 (2 )

2
0
1
(2 )

2 2

1

r 2
h1 = 1
1

4 1 4

1
3
3
10 3 10

1 0 1

0 1 0 ,
0 0 0

1
1
r
r t
h2 = 0 x 2 = 0 e .
1
1


,
A .

25

4 1 4 1
4 1 4 1
1

r
r

(2 )
4
( A 2 E )h3 = h2 12 4 12 0 3 1 3 0

10
10 3 10 1
3 10 1

1 0 1 1
(1)+ (2 )
(2 )+3(1)
1 0 `1 1

(3)+3(2 )
(3)(1)
0 3 ,

3 1 3 0
0 1

0 0 0 0
1 0 1 1

1 1
1
r
r

h3 = 0 + 3 ( = 0 ) h3 = 3 .
1 0
0


2.
1
1 1
x
1

t

t
y = C1 e 2 + e C 2 0 + C 3 t 0 + 3 . n
z
2
1
1 0


2.2. (2-14) x& = 7 x + y + 2 z

y& = 2 x + 3 y + z , (1, 2,3 = 3) .


z& = 8 x 2 y z

1 2
7

d A = 2
3
1 .
8 2 1

1. ,
.
r r
( A E )h1 = 0

26

1
2
4

0
1
A E = 2
8 2 4

1 0

0 1
0 0

2
0,
0

1

1
r
r 2
h1 = 0 h1 = 0 . 2
1

,
A :
r
r
( A E )h2 = h1 .

4
1
2 1

0
1 0
2
8 2 4 2

1 0

0 1
0 0

1 ,
0 0

1
2
0

1
0
0
r
r
2
h2 = 0 + 1 ( = 0 ) h2 = 1 .
0
1 0

r
r
( A E )h3 = h2 .

27

4
1
2 0

0
1 1
2
8 2 4 0

1 0

0 1
0 0

1 1

2 2
0 2 ,
0 0

1 1

0
r
r
2 2
h2 = 0 + 2 ( = 1 ) h3 = 2 .
1
1 0


3.
1 0
x
1



3t
3t
y = C1e 0 + C 2 e t 0 + 1 +
z
2
2 0

2 1 0 0

3t t
+ C 3 e 0 + t 1 + 2 . o
2
2 0 1

2.3. (2-01) x& = 4 x + 3 y

y& = 4 y 3 z
, (1 = 5, 2,3 = 4 3i ) .
z& = x + 3 y + 5 z

0
4 3

e A = 0 4 3 .
1 3
5

1. ,

A .
r r
1 = 5 , ( A 1 E )h1 = 0 .

28

0
1 3

A 1 E = 0 1 3
1 3
0

9
r
h1 = 3 .
1

r r
2 = 4 + 3i , ( A 2 E )h2 = 0 .
A 2 E =

3
0
3i

3
0 3i
1
3 1 3i

1 0 9

0 1 3 ,
0 0 0

1 0 1

i ,
0 1
0 0 0

1
r
h2 = i .
1

1

r


r
x2 = h2 e (4 + 3i )t = i e (4 + 3i )t = e 4t i e 3it =
1
1


cos 3t sin 3t
1


4t
4t
e i (cos 3t + i sin 3t ) = e sin 3t + i cos 3t .
cos 3t sin 3t
1

r
r
r
r
- x 2 = Re x 2 x3 = Im x 2 - -

.
2.
cos 3t
x
9
sin 3t

4t

5t
y = C1 e 3 + e C 2 sin 3t + C 3 cos 3t . p
z
1
sin 3t
cos 3t

29

2.4. (2-41)
e 2t
x& = x + y +

cos t .
y& = 2 x + 3 y
1 1

.
f A =
2 3

1. det ( A E ) = 0 .

1
1
= (1 )(3 ) + 2 = 2 4 + 5 = 0, 2 3
1, 2 = 2 i .
2. ,

A .
r r
1 = 2 + i , ( A 1 E )h1 = 0 .
A 1 E =

1 i 1

2 1 i

1 i

1 + ,
2 2

0
0

r 1
h1 = 2
1

i
r 1 i
r 1

, h1 =
.
2 , h1 =
2
1 + i

r
1 (2+ i )t
r
e

x 1 =
=
h1e 1t =
1 + i
cos t sin t
1 0
+ i
.
e 2t + e it = e 2t
t

t
t
+
t
1
i
cos
sin
cos
sin


r
r
r
r
x1 = Re x 1 x 2 = Im x 1 - .
3.
x
cos t
sin t

= C1 e 2t
+ C 2 e 2t
.
y
cos t sin t
cos t + sin t
30

4. , C1 = C1 (t ) C 2 = C 2 (t ) .

x& = C1 (t )e 2t cos t + C1 (t ) e 2t cos t + C 2 (t )e 2t sin t +

+ C 2 (t ) e 2t sin t

y& = C1 (t )e 2t (cos t sin t ) + C1 (t ) e 2t (cos t sin t ) +

+ C 2 (t )e 2t (cos t + sin t ) + C 2 (t ) e 2t (cos t + sin t )


,

C1 C 2

(
(

)
)


e 2t

2t
2t
=
C1 (t )e cos t + C 2 (t )e sin t
cos t ,

C (t )e 2t (cos t sin t ) + C (t )e 2t (cos t + sin t ) = 0


2
1
e 2t , cos t
C (t ) cos 2 t + C (t ) sin t cos t
=1
2
,
1
C1 (t )(cos t sin t ) + C 2 (t )(cos t + sin t ) = 0

, 2, , (cos t + sin t )
C (t ) cos 2 t + C (t ) sin t cos t
=1
1
2
,

2

2
2
C1 (t ) cos t sin t + C 2 (t )(cos t + sin t ) = 0
, 2
C (t ) C (t ) = 2
1
2
.

C1 (t )(cos t sin t ) + C 2 (t )(cos t + sin t ) = 0

C1 = C 2 + 2

2 C 2 + 1 cos t = 2 sin t ,

31

d cos t
sin t

dt + c 2 =
C 2 (t ) = 1 +
dt + c 2 = t
cos t
cos t

= t ln cos t + c 2 ,

sin t
C1 (t ) = 1 +
dt + c1 = t ln cos t + c1 .
cos t

x
cos t 2t
= (t ln cos t + c1 )
e +
y
cos t sin t

( t ln cos t + c 2 )

2t
e . q
cos t + sin t
sin t

2.6.

:
x& = 4 x + 3 y

29. (2-01) y& = 4 y 3z


, ( 1 = 5 , 2,3 = 4 3i ).
z& = x + 3 y + 5 z

x& = 2 x y + z

30. (2-02) y& = 2 x 5 y + 2 z , ( 1, 2,3 = 3 ).


z& = 3 x 2 y 2 z

x& = 3x + 2 y

31. (2-03) y& = 3 y + z


, ( 1 = 4 , 2,3 = 3 2i ).
z& = 2 x 4 y + 4 z

x& = 4 x + 2 y 3z

32. (2-04) y& = 2 y + z


, (1, 2,3 = 2) .
z& = x y

32

x& = 3 x + y 2 z

33. (2-11) y& = 5 y 3 z


, ( 1 = 2 , 2,3 = 3 i ).
z& = x + 3 y

x& = 6 x + y + 2 z

34. (2-12) y& = 2 x + 2 y + z , (1, 2,3 = 2) .


z& = 8 x 2 y 2 z

x& = 4 x 5 y + 5 z

35. (2-13) y& = 3x 2 y + 5 z , ( 1 = 1 , 2,3 = 1 i ).


z& = x + 2 y z

x& = 7 x + y + 2 z

36. (2-14) y& = 2 x + 3 y + z , (1, 2,3 = 3) .


z& = 8 x 2 y z

x& = 4 x + 2 y + 5 z

37. (2-21) y& = 6 x y 6 z , (1, 2 = 1, 3 = 2) .


z& = 8 x + 3 y + 9 z

x& = x + y z

38. (2-22) y& = x + 2 y z , (1, 2 = 2, 3 = 3) .


z& = 2 x y + 4 z

x& = 2 x + y + z

39. (2-23) y& = 2 x z


, (1, 2 = 1, 3 = 2) .
z& = 2 x + y + 2 z

x& = 5 x y 4 z

40. (2-24) y& = 12 x + 5 y + 12 z , (1 = 1, 2,3 = 1) .


z& = 10 x 3 y 9 z

x& = 4 x + y

41. (2-31) y& = x 4 y 2 z , (1 = 3, 2,3 = 2 i ) .


z& = 5 x + 5 y + z

33

x& = 3 x z

42. (2-32) y& = 4 x 2 y 3 z , (1 = 0, 2,3 = 1) .


z& = 4 x + 2 y + 3z

x& = 4 x 3 y + z

43. (2-33) y& = x 2 y + 3z , (1 = 2, 2,3 = 1 2i ) .


z& = 5 x 5 y + 2 z

x& = x + 2 y z

44. (2-34) y& = x 3 y + z , ( 1, 2,3 = 2) .


z& = y 2 z

e 2t
x& = x + y +
45. (2-41)
cos t ,
y& = 2 x + 3 y
x& = 2 x + y + t t e 3t
,
46. (2-42)
y& = x + 4 y
1

x& = y + cos t
47. (2-43)
,
1
y& = x +
sin t

x& = 3 x 2 y
,
48. (2-44)
t
y& = 2 x y + 15e t
x& = 4 x + y + 2 z

49. (2-51) y& = y + z


, (1 = 1, 2,3 = 1 i ) .
z& = 6 x + 2 y + 2 z

x& = 3x + y z

50. (2-52) y& = 4 x + 5 y 2 z , (1 = 3, 2,3 = 1) .


z& = 8 x + 6 y 3z

34

x& = 2 y z

51. (2-53) y& = 2 x + 4 y + 2 z , (1 = 2, 2,3 = 1 i ) .


z& = 2 x 2 y

x& = 7 x + 10 y + 8 z

52. (2-54) y& = x + z


, (1 = 1, 2,3 = 2) .
z& = 3x + 6 y + 4 z

x& = 3x + y + z

53. (2-61) y& = x + 3 y + z , (1 = 2, 2,3 = 4) .


z& = 2 x 2 y + 4 z

x& = 3x 3 y 6 z

54. (2-62) y& = y + 4 z


, (1 = 3, 2,3 = 1) .
z& = y 3z

x& = 2 x + y z

55. (2-63) y& = x + 3 y z , (1 = 1, 2,3 = 2) .


z& = x + 2 y

x& = 3 x y

56. (2-64) y& = 4 x + y


, (1 = 2, 2,3 = 1) .
z& = 2 x + y 2 z

2.7. :
x
sin 3t
cos 3t
9

5t
4t
4t
29. y = C1e 3 + C 2 e sin 3t + C3 e cos 3t
z
sin 3t
cos 3t
1

35

1 0
x
1


3t
3t
30. y = C1e 2 + C 2 e t 2 + 0 +
z
1
1 1

+ C3 e

3t

2
t
2

1 0 1

2 + t 0 + 1
1 1 0

2
sin 2t
cos 2t
x

4t
3t
3t
31. y = C1e 1 + C 2 e sin 2t + C 3 e cos 2t
1
2 sin 2t
2 cos 2t
z

1 0
x
1


2t
2t
32. y = C1e 1 + C 2 e t 1 + 2 +
z
0
0 1

2 1 0 0
t
+ C 3 e 2t 1 + t 2 + 3
2
0 1 2

2 sin t + cos t
x
1
2 cos t sin t

33. y = C1e 2t 1 + C 2 e 3t 3 cos t + C 3 e 3t 3 sin t


2 sin t cos t
z
1
sin t + 2 cos t

1 0
x
1



34. y = C1e 2t 0 + C 2 e 2t t 0 + 1 +
z
2
2 0

2 1 0 0
t
+ C 3 e 0 + t 1 + 2
2
2 0 1

2
cos t 2 sin t
2 cos t + sin t
x

t
t
t
sin t
cos t
35. y = C1e 1 + C 2 e

+ C3 e
1

cos t
z

t
sin

2t

36

1 1
x
1



3t
3t
36. y = C1e 0 + C 2 e t 0 + 1 +
z
2
2 2

2 1 1 1
t
+ C 3 e 0 + t 1 + 1
2
2 2 1

1 1
x 1
1
t


37. y = C1 0 + C 2 t 0 + 3 e + C3 2 e 2t

z 1
2


1 0
3t

1
1 0
x
2


3t
38. y = C1 1e + C2 0 + C3 t 0 + 1 e 2t
1 0
z
3
1




0
0 1
x
1


2t
39. y = C1 2 e + C 2 1 + C 3 t 1 + 1 e t

z
2
1


1 0

1
1 1
x
1

t

t
40. y = C1e 2 + e C 2 0 + C3 t 0 + 3
z
2
1
1 0



cos t
sin t

1
x

3t

41. y = C1 1 e + C 2 2 cos t sin t + C 3 2 sin t + cos t e 2t

sin t 2 cos t

0
z



cos t + 2 sin t

1 1
x 1


42. y = C1 2 + C2 t 2 +
2
z 2

37

2
2
t

0 e + C3 5
6
0

3 cos 2t + sin 2t
x
1
3 sin 2t cos 2t

2t

43. y = C11e + C2 4 cos 2t + 3sin 2t + C3 4 sin 2t 3 cos 2t et



z
1

5 cos 2t
5 sin 2t

1 1

2 1 1 1
t 2t
0 + t 1 + 0 e .
2
1 0 0

44. y = C1 0 + C2 t 0 + 1 + C2


1
1 0

2t
sin t
cos t 2t
x
e ,
e + C 2 (t )
45. = C1 (t )
cos t + sin t
cos t sin t
y
z

C1 (t ) = t ln cos t + c1 , C 2 (t ) = t ln cos t + c 2 .
x

1 0

46. = C1 (t ) + C 2 (t ) t + e 3t ,
1
1
1
y



2 3
2 2
2
C1 (t ) = t t + t t + c1 , C 2 (t ) = t 2 t + c 2 .
7
5
5
sin t
cos t
x
, C1 (t ) = c1 ,
+ C 2 (t )
47. = C1 (t )
cos t
sin t
y

C 2 (t ) = ln sin t ln cos t + c 2 .
x

1 0

48. = C1 (t ) + C 2 (t ) 2t + e t ,
y
1
1
1
C1 (t ) = 12t

t + c1 , C 2 (t ) = 10t t + c 2 .

cos t + sin t
sin t cos t
x
1


t
49. y = C1 3 e + C 2 2 sin t + C 3 2 cos t e t

2 sin t
z
0



2 cos t
1
1 1
x
0


3t
50. y = C1 1 e + C 2 0 + C 3 t 0 + 1 e t

z
1
2


2 0

38

cos t + sin t
x
1
cos t sin t

2t

51. y = C1 1e + C2 2 cos t + C3 2 sin t et


2 cos t
z
0
2 sin t


2
2 0
x
1


t
52. y = C1 0 e + C 2 1 + C 3 t 1 + 1 e 2t

z
1
0


0 1

1
1 0
x
1


2t
53. y = C1 0 e + C 2 1 + C3 t 1 + 0 e 4t

z
1
0


0 1

0
0 3 4
x
1


3t

54. y = C1 0 e + C 2 2 + C 3 t 2 + 1 e t

z
0

1


1 0

0
0 1
x
1


t
55. y = C1 0 e + C 2 1 + C 3 t 1 + 0 e 2t

z
1
1


1 0

1
1 0
x
0


2t
56. y = C1 0 e + C2 2 + C3 t 2 + 1 e t
0 1
z
1
0



39